Clinicopathological profile of adenoid cystic carcinoma of minor salivary gland tumour: our experience at a tertiary care centre - Doddrangaiah, Prakash Mylanahalli; Karunakaran, Bharath Kanna; Mallali, Roopa S.; Fathima, Afshan (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Adenoid cystic carcinoma (ACC) is a rare malignant tumour originating from minor salivary glands. It is known for perineural spread, local recurrences and distant metastasis. The minor salivary gland tumour represents 3% of all head and neck neoplasms, whereas ACC constitutes about 0.5% of all malignant salivary gland neoplasms. This study was done to evaluate the clinical presentation and histopathological findings of minor salivary gland tumour. Methods: This study was done in the department of ENT, Bangalore Medical College and Research Institute from May 2017 to July 2019. Of the 25 patients with minor salivary gland tumour, 10 patients with ACC were considered for the present study. A detailed clinical and histopathological evaluation was done. Results were documented and tabulated in excel sheet. Results: We analysed data of 25 (16 female, 9 male) patients in the age group of 30-60 years, of which 10 patients had adenoid cystic carcinoma of minor salivary gland tumour. The most frequent site of tumour occurrence was noted in the hard palate (6 patients), followed by retromolar trigone (2 patients), floor of mouth (1 patient) and tongue (1 patient). The histopathological pattern noted most commonly in our study: cribriform pattern (6 cases), tubular (1 case) and solid (3 cases). Conclusions: ACC of minor salivary glands is rare. The otorhinolaryngologist should bear this clinical entity in mind when encountered with a painless swelling over the hard palate. This would lead to an early diagnosis and prompt management in such patients.